Can the Right Composition and Diversity of Farmed Species Improve Food Security Among Smallholder Farmers? - MacLaren, Chloe; Aliyu, Kamaluddin Tijjani; Waswa, Wycliffe; Storkey, Jonathan; Claessens, Lieven; Vanlauwe, Bernard; Mead, Andrew (Frontiers in Sustainable Food Systems, 2022)
Food security and livelihoods among smallholder farmers in sub-Saharan Africa are often constrained by limited farm resource endowment. It can be difficult to improve resource endowment given barriers such as low land availability and the unaffordability of agricultural inputs, so here we ask whether farmers can gain a better return on their resources through optimising their farm strategy in terms of the composition and/or diversity of crop and livestock species raised. Our survey of 1133 smallholder farmers in western Kenya and northern Nigeria, using a modified version of RHoMIS, suggested that choice of farm strategy can have a substantial positive impact on food security and farm incomes. In particular, we found that it was possible for farms with a high species richness but low resource endowment to achieve similar or better food security and income outcomes than farms with low species richness and high resource endowment. This indicates strong potential for diversification to improve food security and livelihoods among smallholder farmers. However, we noted some exceptions to this trend that require further investigation: increasing species richness was not beneficial for low-resourced, livestock-focused farmers in western Kenya, and increasing species richness was associated with a decline in dietary diversity in northern Nigeria (due to declines in purchased dietary diversity that outweighed increases in on-farm and other sources of dietary diversity). Further research applying similar analyses to a wider RHoMIS dataset covering a greater diversity of countries and agro-ecological zones could help to identify where, and why, different farm strategies result in better or worse outcomes for smallholder farmers.